Design of broadband high efficiency absorption antenna based on metamaterial nano-ring array - Li, Na; Tian, Yanwei; Bao, Jianqiang; Wang, Yan; Zhao, Chi (Frontiers in Materials, 2022)
Compared with the traditional solar cells, the nano-optical antenna breaks through the band-gap limitation of semiconductor materials, and provides a new scheme for solar energy collection. In order to solve the problems of complex structure, low efficiency and narrow bandwidth of nano-optical antenna, a novel nano-annular array antenna based on metamaterials is proposed in this paper. The antenna has an average absorption efficiency of 96.93% in the wide-band absorption range of visible and near-infrared light. First of all, the basic design theory of this antenna was given based on the surface plasma theory. Then, the antenna structure design scheme was determined, which was consists of only two layers of metal and a layer of Al2O3 dielectric insulation. Finally, based on the established antenna model, its absorption characteristics was analyzed through the simulation analysis. The analysis result shows that the super-absorption ability of the antenna is independent of the polarization of the incident light, and the average absorption ability can be maintained at about 91% when the incident angle is ±60°. The absorption capability of the antenna is mainly due to the synergistic effect of Fabry-Perot resonance and local Surface plasmon resonance enhancement. This conclusion can provide the theoretical guidance for the structural design of this kind of antenna.